Design and Synthesis of New Hybrid Molecules That Activate the Transcription Factor Nrf2 and Simultaneously Release Carbon Monoxide. Issue 45 (15th September 2014) - Wilson, Jayne Louise; Fayad Kobeissi, Sarah; Oudir, Souhila; Haas, Benjamin; Michel, Brian; Dubois Randé, Jean‐Luc; Ollivier, Anthony; Martens, Thierry; Rivard, Michael; Motterlini, Roberto; Foresti, Roberta
Abstract The transcription factor Nrf2 and its downstream target heme oxygenase‐1 (HO‐1) are essential protective systems against oxidative stress and inflammation. The products of HO‐1 enzymatic activity, biliverdin and carbon monoxide (CO), actively contribute to this protection, suggesting that exploitation of these cellular systems may offer new therapeutic avenues in a variety of diseases. Starting from a CO‐releasing compound and a chemical scaffold exhibiting electrophilic characteristics (esters of fumaric acid), we report the synthesis of hybrid molecules that simultaneously activate Nrf2 and liberate CO. These hybrid compounds, which we termed "HYCOs", release CO to myoglobin and activate the CO‐sensitive fluorescent probe COP‐1, while also potently inducing nuclear accumulation of Nrf2 and HO‐1 expression and activity in different cell types. Thus, we provide here the first example of a new class of pharmacologically active molecules that target the HO‐1 pathway by combining an Nrf2 activator coordinated to a CO‐releasing group.